Feasibility of elastomeric composites as alternative materials for marine applications: A compendious review on their properties and opportunities. (November 2022) - Aravind, D; Senthilkumar, K; Rajini, N; Muthu Kumar, T Senthil; Chandrasekar, M; Ismail, Sikiru O; Yeetsorn, Rungsima; Parameswaranpillai, Jyotishkumar; Siengchin, Suchart; Indira Devi, MP
The term elastomer is a curtailment of two words, which are elastic and polymers. Accordingly, elastomers are polymer materials with elasticity. The significant challenges hindering the development of materials for naval applications, similar to other engineering sectors, include achieving a competitive light elastomeric structure. Marine structures are susceptible to various damage responses due to various loads throughout their service life. Being flexible, elastomer has a low modulus of elasticity, exhibits higher values of failure strain and yield strength. In these regards, elastomers are attractive materials for applications that require elasticity because they offer substantial advantages compared to traditional materials. However, the low fire resistance of these elastomeric materials jeopardizes their use in some critical applications. As a result, elastomeric blends and composites containing flame retardant (FR) additives are commonly used. On the other hand, elastomers possess (i) high strength-to-weight ratio, (ii) excellent impact properties, (iii) low infrared, magnetic, and radar signatures, (iv) excellent durability, and (v) high resilience to extreme loads. Hence, the scope of this study focuses on review and awareness regarding the feasibility of marine applications of elastomers/elastomeric composites, their current scientific and technological drawbacks, and future outlooks or prospects to support several applications in the marine industry.